Preliminary Design of Propylene Glycol Plant from Propylene Oxide and Water Using Acid Catalyst Capacity of 60,000 Tons/Year - Anggraeni, Diah Ayu; , Eni Budiyati, S.T., M.Eng; , Ir. Nur Hidayati, M.T., Ph.D (2016)
Propylene glycol is produced through the hydration reaction of propylene oxide and water with sulfuric acid catalyst. The reaction takes place in the liquid phase under a temperature of 30°C and a pressure of 1 atm. To purify propylene glycol, distillation process is carried out in order to obtain products of propylene glycol with a purity of 99.99%. Propylene glycol plant with a capacity of 60,000 tons per year requires the raw material propylene oxide of 55,508.77 tons per year and as much water as 5.87 tons per year. The plant was planned to be established in Gresik, East Java with land area of 8,575 m2. Utilities supporting processes include water supply of 42,505.13 kg per hour which are processed from Bengawan Solo River, provision of saturates steam per hour 87,545,513.56 Btu/h. The plant's electricity requirements are 286.46 kW, in the form of diesel fuel requirements 2,349.48 liters/hour and the requirement for compressed air for instrumentation 179.99 m3/h. The economic analysis results show that Percent Return On Investment (ROI) before tax is 32.37% and after tax is 22.66%. Pay Out Time (POT) before tax is 2.36 year and Pay Out Time (POT) after tax is 3.06 year. Break Even Point (BEP) of 46.64%, Shut Down Point (SDP) amounted to 22.74%, and Discounted Cash Flow (DCF) of 30.28%, were obtained from the data result of feasibility analysis can be concluded that the plant is profitable and feasible to be established.